Misperceptions, inactivity and maternal factors may drive obesity among Barbadian adolescents - Gaskin, Pamela S; Broome, Hedy; Alert, Colin; Fraser, Henry (Public health nutrition, 2008)
To describe (1) the prevalence of overweight and obesity and their association with physical activity; (2) the effect of different cut-off points for body mass index (BMI) on weight status categorisation; and (3) associations of weight status with perceptions of body size, health and diet quality. A cross-sectional study. Secondary schools in Barbados. A cohort of 400 schoolchildren, 11-16 years old, selected to study physical education practices. Prevalence of overweight (15% boys; 17% girls) and obesity (7% boys; 12% girls) was high. Maternal obesity, as defined by the International Obesity Task Force (IOTF) BMI cut-off points, predicted weight status such that reporting an obese mother increased the odds of being overweight by 5.25 (95% confidence interval: 2.44, 11.31). Physical activity was inversely associated with weight status; however levels were low. Recreational physical activity was not associated with weight status in either category. Overweight subjects tended to misclassify themselves as normal weight and those who misclassified perceived themselves to be of similar health status to normal-weight subjects. The National Center for Health Statistics and IOTF BMI cut-off points produced different estimates of overweight and obesity. Our findings suggest that inadequate physical activity and ignorance related to food and appropriate body size are promoting high levels of adiposity with a strong contribution from maternal obesity, which may be explained by perinatal and other intergenerational effects acting on both sexes. Prevalence studies and local proxy tools for adiposity assessment are needed.